PROFESIONALISME PEGAWAI NEGERI SIPIL KECAMATAN LANDASAN ULIN KOTA BANJARBARU - Ade Hermawan (Universitas Tribhuwana Tunggadewi, 2017)
ABSTRACT : Civil Service Platform Ulin District of Banjarbaru professional work. The proof is the third indicator that researchers make a measure to assess the professionalism of the Civil Service Platform Ulin District of Banjarbaru namely work ability, work skills, and work experience, all of them showed good results. Efforts to increase the professionalism of the Civil Service in the District of Runway Ulin Banjarbaru done through rekreuitment employees in accordance with the needs of the organization and corruption-free , design work , arranged on the pattern of the employment relationship, work assessment carried out by an instrument Rate Job Performance Employees (PPKP) consisting of a Target Job employees (SKP) and Conduct of work , education and training of employees through leadership training , functional training and technical training, improving the discipline to enforce disciplinary rules in accordance with applicable regulations. Keyword: Professionalism, PNS. Pegawai Negeri Sipil Kecamatan Landasan Ulin Kota Banjarbaru profesional dalam bekerja berdasarkan indikator penelitian yang semuanya menunjukkan baik. Indikator yang digunakan dalam penelitian tersebut yaitu kemampuan kerja, keterampilan kerja, dan pengalaman kerja. Upaya peningkatan Profesionalisme Pegawai Negeri Sipil di Kecamatan Landasan Ulin Kota Banjarbaru dilakukan melalui rekreuitmen pegawai yang sesuai dengan kebutuhan organisasi dan bebas KKN, rancangan pekerjaan disusun berdasarkan pola hubungan pekerjaan, penilaian kerja dilakukan melalui instrumen Penilaian Prestasi Kerja Pegawai (PPKP) yang terdiri dari Sasaran Kerja Pegawai (SKP) dan perilaku kerja, pendidikan dan pelatihan pegawai melalui diklat kepemimpinan, diklat fungsional dan diklat teknis, peningkatan disiplin dengan penegakan aturan disiplin sesuai peraturan yang berlaku. Kata Kunci: Profesionalisme, PNS.